PENGARUH PENGENDALIAN INTERNAL DAN KOMPENSASI TERHADAP KECURANGAN PADA CV PRIMA SUGIH ABADI DI PEKANBARU - Saputri, Marlinda; Sofyan, Deviana; Setiawati, Setiawati (Jurnal Daya Saing, 2024)
Abstract: The purpose of this research is to determine the effect of internal control and compensation on fraud at CV Prima Sugih Abadi in Pekanbaru. The population used in this research was all employees at CV Prima Sugih Abadi, totaling 79 people. The data collection technique used in this research consists of documentation and questionnaires. Meanwhile, the type of data used is quantitative and qualitative. The data analysis used is multiple linear regression analysis. The research results show that partially internal control does not have a significant influence on fraud and compensation has a significant influence on fraud at CV Prima Sugih Abadi Pekanbaru. Simultaneously, internal control and compensation have a significant influence on fraud at CV Prima Sugih Abadi Pekanbaru. Keywords: Internal Control, Compensation, Froud